Analisis Strategi Pelayanan Front Liner Untuk Memuaskan Nasabah Pada Pt Bank Central Asia Tbk Capem Mayor Oking - Widjojo, Adi S; Suardy, Weman (STIE Kesatuan, 2010)
Service representative is an activity to gift of service from one the side of other side, so that full fill requirement and satisfy to accepting it. With efficient and effective good service will push client to be devoted and loyal to company, because what their want and needed is fulfilled. Target of this research is to know how far quality service have been given by front liner Bank Central Asia to customer, to get customer satisfaction. Method used by writer to answer question from identifying existing problem, by using descriptive method with approach of survey, where research of survey is research taking sample from one population and use questioners as a mean of assist fundamental, where questionaire used to measure relation between service with satisfaction of consumer. Result of this research indicate that service given by PT. Bank Central Asia Capem Mayor Oking in this time is very good with average value 62,62. While satisfaction of customer at the moment to BCA Mayor Oking through analysis of regression got by result for the price of Y = 27,853 + 0,560 X, meaning that satisfaction of customer at Bank Central Asia with service (X) added by 1 becoming 28,42. From result of calculation of correlation analysis got result of that happened positive and middle between quality service frontliner and customer satisfaction with value of correlation coefficient equal to 0,554. After that to analyze coefficient of determinacy to measure service contribution percentage given by BCA Mayor Oking to get customer satisfaction is got result of that service only owning contribution equal to 30,7% and the rest equal to 69,3% influenced by other factor